Karakteristik dan Indeks Massa Tubuh Pecandu Tuak di Kelurahan Botang Kecamatan Makale Kabupaten Tana Toraja - Lisa; Salki Sasmita (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2020)
Tuak is one of traditional drink that containing alcohol in Tana Toraja. It was routinely served in several traditional ceremonies, even many of local people consume it daily. This study aims to describe demography and body mass index of tuak addict (alcoholic) in adult and using description approah over it. There were 50 adult men who were interviewed while measuring their weight and height. All of them were alcoholics. The results of this study showed that 16 participants (32%) were the farmers, 11 participants (22%) were the civil servants and entrepreneurs , 18 % were the students in college, and 6% were the students in school. After measuring their body mass index, there were 32 participants (64%) had a less/over body mass index and 18 participants (36%) had a normal body mass index. Alcoholic drinks are known as one of the factors that can cause abnormal body weight. Whether it's obesity or weight loss. Furthermore, it will be many cases of heart and kidney diseases so that it should be eliminated by involving local community roles.